Field experience with obfuscating million‐user iOS apps in large enterprise mobile development. (8th November 2018) - Wang, Pei; Wu, Dinghao; Chen, Zhaofeng; Wei, Tao
Summary: In recent years, mobile apps have become the infrastructure of many popular Internet services. It is now common that a mobile app serves millions of users across the globe. By examining the code of these apps, reverse engineers can learn various knowledge about the design and implementation of the apps. Real‐world cases have shown that the disclosed critical information allows malicious parties to abuse or exploit the app‐provided services for unrightful profits, leading to significant financial losses. One of the most viable mitigations against malicious reverse engineering is to obfuscate the apps. Despite that security by obscurity is typically considered to be an unsound protection methodology, software obfuscation can indeed increase the cost of reverse engineering, thus delivering practical merits for protecting mobile apps. In this paper, we share our experience of applying obfuscation to multiple commercial iOS apps, each of which has millions of users. We discuss the necessity of adopting obfuscation for protecting modern mobile business, the challenges of software obfuscation on the iOS platform, and our efforts in overcoming these obstacles. We especially focus on factors that are unique to mobile software development that may affect the design and deployment of obfuscation techniques. We report the outcome of our obfuscation with empirical experiments. We additionally elaborate on the follow‐up case studies about how our obfuscation affected the app publication process and how we responded to the negative impacts. This experience report can benefit mobile developers, security service providers, and Apple as the administrator of the iOS ecosystem.